1996
DOI: 10.1111/j.1365-2672.1996.tb03534.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymerase chain reaction assay for the detection and speciation of thermophilic Campylobacter spp.

Abstract: A novel PCR amplification method is described which is specific for the thermophilic, enteropathogenic species Campylobacter jejuni, Camp. coli and Camp. upsaliensis. Rapid, accurate speciation of amplified strains is possible on the basis of restriction fragment length polymorphisms of PCR products digested with three restriction enzymes, AluI, DdeI and DraI. The sensitivity of detection is 25 cfu in water, and 2 x 10(3) cfu in full cream milk. An epidemiological application of the assay in detecting non-cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…The Bolton broth culture was inoculated onto modified charcoal cefoperazone deoxycholate agar (Oxoid, Inc.) by using a cotton-tipped swab followed by streaking. After 48 h of incubation, presumptive Campylobacter colonies (small, grey, moist, and flat spreading or droplike; five per sample) were transferred to blood agar plates and incubated for 24 h. Morphological examinations, catalase and oxidase tests, and species-specific PCR assays were performed as described previously (16,23,28). After confirmation, up to three Campylobacter isolates per sample were stored at 280uC in brain heart infusion broth with 30% glycerol in cryogenic vials.…”
Section: Methodsmentioning
confidence: 99%
“…The Bolton broth culture was inoculated onto modified charcoal cefoperazone deoxycholate agar (Oxoid, Inc.) by using a cotton-tipped swab followed by streaking. After 48 h of incubation, presumptive Campylobacter colonies (small, grey, moist, and flat spreading or droplike; five per sample) were transferred to blood agar plates and incubated for 24 h. Morphological examinations, catalase and oxidase tests, and species-specific PCR assays were performed as described previously (16,23,28). After confirmation, up to three Campylobacter isolates per sample were stored at 280uC in brain heart infusion broth with 30% glycerol in cryogenic vials.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that the repair of water mains most probably resulted in contamination and that nonchlorinated ground-water systems may be susceptible to contamination by campylobacters. Jackson et al (1996) developed a novel PCR assay for the detection and speciation of C. jejuni, C. coli and C. upsaliensis. The primers BO4263 and BO4264 (Table 6) amplify a 256-bp sequence of a novel open reading frame adjacent to and downstream of a novel C. jejuni two-component regulator gene.…”
Section: Pulsed Field Gel Electrophoresis (Pfge)mentioning
confidence: 99%
“…A number of PCR assays have been described for the detection of campylobacters from food and faecal samples (1, 4, 6, 13, 14). The present study was carried to access the prevalence of C. jejuni in various food and faecal samples and to compare the efficacy of cultural and biochemical tests with PCR for detection of the organism.…”
Section: Introductionmentioning
confidence: 99%